Macronutrient availability and maize yield after swine slurry applications to an oxisol Disponibilidade de macronutrientes e rendimento de milho em latossolo fertilizado com dejeto suíno - da Costa A.C.* (2012)
Swine manure (SM) applications to maize under no-tillage were tested in a 10-year field experiment to define the appropriate rates. The responses in yield and soil property to the treatments were evaluated: SM at rates of 0, 25, 50, 100 and 200 m3 ha-1; soluble fertilizer (SF); and SM plus soluble fertilizer (SM + SF), all annually spread on the soil surface. The soil pH was not affected by SM, but at rates > 100 m3 ha-1, the exchangeable Ca and available P and K increased in the 0-5 cm and exchangeable Al decreased in 20-40 cm layer. In the surface layer (0-5 cm), SF reduced the pH and increased the content of soil exchangeable Al compared to the other treatments. The mean annual maize yield increased with increasing SM rates, fitting a quadratic model, and reached 90% of the maximum at a rate of 84 m3 ha-1. The SM applied annually to the soil surface did not affect soil pH, but generally improved soil nutrient availability, at rates > 50 m3 ha-1.